Minutes of Twenty-fifth Regular Meeting (Rocky Mountain Coal Mining Institute, 1927)
The twenty-fifth regular meeting of the Rocky Mountain Coal Mining Institute was called to order at 11 a. m. Monday, August 29, 1927, in the County Court House at Trinidad, Colorado, the Vice-President, F. L. Peart, presiding. After a few words from John F. Carmody, Editor of Goal Age, J. Q. McNatt, Division Engineer of the Colorado Fuel & Iron Company, read a paper on "Coal Geology." In the afternoon, Prof. C. B. Carpenter, of the Colorado School of Mines talked on the work in Fuel Engineering being developed at the Colorado School of Mines. W. C. Holman, of the Phelps Dodge Corporation, then read his paper on "Developing a Pit Car Design." L. M. Kuhns, Safety Engineer of the Gallup American Coal Company, read his paper on "Safety Methods at Gallup American No. 5 Mine." After discussion the meeting adjourned for the day.